Justification of principles for healthcare priority setting: the relevance and roles of empirical studies exploring public values - Gustavsson, Erik (Journal of medical ethics, 2025)
How should scarce healthcare resources be distributed? This is a contentious issue that became especially pressing during the pandemic. It is often emphasised that studies exploring public views about this question provide valuable input to the issue of healthcare priority setting. While there has been a vast number of such studies it is rarely articulated, more specifically, what the results from these studies would mean for the justification of principles for priority setting. On the one hand, it seems unreasonable that public values would straightforwardly decide the ethical question of how resources should be distributed. On the other hand, in a democratic society, it seems equally unreasonable that they would be considered irrelevant for this question. In this paper we draw on the notion of reflective equilibrium and discuss the relevance and roles that empirical studies may plausibly have for justification in priority setting ethics. We develop a framework for analysing how different kinds of empirical results may have different kinds of implications for justification.